Current Drug Repurposing Strategies for Rare Neurodegenerative Disorders - Shah, Sweta; Dooms, Marc Marie; Amaral-Garcia, Sofia; Igoillo-Esteve, Mariana (Frontiers in Pharmacology, 2021)
Rare diseases are life-threatening or chronically debilitating low-prevalent disorders caused by pathogenic mutations or particular environmental insults. Due to their high complexity and low frequency, important gaps still exist in their prevention, diagnosis, and treatment. Since new drug discovery is a very costly and time-consuming process, big pharmaceutical companies show relatively low interest in orphan drug research and development due to the high cost of investment compared to the low market return of the product. Drug repurposing-based approaches appear then as cost- and time- saving strategy for the development of therapeutic opportunities for rare diseases. In this manuscript we will discuss the scientific, regulatory, and economic aspects of the development of repurposed drugs for the treatment of rare neurodegenerative disorders with a particular focus on Huntington’s disease, Friedreich’s ataxia, Wolfram syndrome and Amyotrophic Lateral Sclerosis. The role of academia, pharmaceutical companies, patient associations and foundations on the identification of candidate compounds, and their preclinical and clinical evaluation will also be discussed.